Veno-occlusive disease of the liver - Tınaztepe, Behçet; Tınaztepe, Keriman; Uzunalimoğlu, Bedri (The Turkish Journal of Pediatrics, 1967)
Presented here are the first two case reports of veno-occlusive disease occurring in Turkish children, along with a brief review of the pertinent literature. The condition was found to be rare among Turkish children whose clinical history suggests cirrhosis. No cirrhosis was found in these two patients, and, in the pathogenesis of 100 cases of cirrhosis treated at Hacettepe Children's Hospital, veno-occlusive disease had no significant rôle.